滚子摆动从动件盘状凸轮轮廓曲线的确定 - 阮晓光; 蔡安江 (Jixie chuandong)
The discal cam contour line with the driven part of roller swing is used in the double piston pump transport mechanism,By analyzing the working principal and the movements of this pump transport mechanism,the contour line of the compensatory cam mechanism — the discal cam contour line with the driven part of roller swing is given,and gain preferable effect is gein in the application.